Instrumentation for audiology and hearing science : theory and practice - Silman, Shlomo; Emmer, Michele B., 1951-; Silverman, Carol A. (Carol Ann), 1953-; Brody, Alexa (San Diego, CA : Plural Publishing, Inc., 2023)
'Understanding the array and complexity of instrumentation available to audiologists and hearing scientists is important to students, beginning clinicians, and even seasoned professionals. The second edition of Instrumentation for Audiology and Hearing Science: Theory and Practice is a comprehensive and accessible look at instrumentation used in these fields for research and clinical purposes. The expert authors introduce the laws of physics as they relate to audiology and hearing science and explain a range of concepts in electronics directly related to instrumentation used in audiology and hearing science, such as filtering and immittance (involving acceptance i.e., admittance, and rejection i.e., impedance of energy), explain the fundamental instrumentation concepts in mathematics, physics, and electronics in a systematic manner including only the necessary formulae and basic scientific principles'--
General physics and introduction to sound energy -- Electrical energy : direct current -- Electrical energy : alternating current -- Filtering and electrical impedance -- Building communication systems : evolution from analog to digital -- Acoustic immittance -- Amplification -- Assistive listening devices -- Vestibular assessment : electronystagmography and videonystagmography -- Test equipment used in audiology and hearing science -- Instrumentation for calibration and calibration of test stimuli.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
OCLC control number change - WorldCat record variable field(s) change: 650
Keywords: Audiology -- instrumentation; Hearing Tests -- instrumentation; Audiology -- Instruments; Audiology -- Instruments